2018
DOI: 10.3390/cryst8100367
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controllable Synthesis of Zeolitic Imidazolate Framework/Carbon Nanotube Composites

Abstract: Composite materials that combine the unique properties of zeolitic imidazolate frameworks (ZIFs) and carbon nanotubes (CNTs) can give rise to novel applications. Here, ZIF-8/CNT composites were successfully prepared with and without the addition of an agent template. The size of the ZIF-8 crystals in the composite materials was controlled by varying the template, feeding order, and concentration of reactants. Thus, ZIF-8 crystals with a wide variety of sizes (from nano- to micrometer size, which is range that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Using ordered species to fill the connected vessels can be represented by filling a single-crystal lattice which describes the three-dimensional ordering of structural motifs of crystals. However, this is generally difficult to realize experimentally because conucleation and growth inside the connected vessels usually lead to lattice domains which are confined to a short range, forming polyoriented domains (polycrystals) or nanosized domains (nanocrystals) (Figure S2). , It has been reported that a single crystal can incorporate discrete species inside, which means that it is possible to fill the single crystals across several branches of a specific type of the connected vessels, the connected spaces inside 3D networks. , By carefully controlling the crystallization kinetics, single crystals have been successfully grown inside templates with ordered porous structures. In these cases, multiple channels are occupied by a single crystal. After careful surveying of these reports, we noticed that these single crystals could be distinguished into two types.…”
Section: Introductionmentioning
confidence: 99%
“…Using ordered species to fill the connected vessels can be represented by filling a single-crystal lattice which describes the three-dimensional ordering of structural motifs of crystals. However, this is generally difficult to realize experimentally because conucleation and growth inside the connected vessels usually lead to lattice domains which are confined to a short range, forming polyoriented domains (polycrystals) or nanosized domains (nanocrystals) (Figure S2). , It has been reported that a single crystal can incorporate discrete species inside, which means that it is possible to fill the single crystals across several branches of a specific type of the connected vessels, the connected spaces inside 3D networks. , By carefully controlling the crystallization kinetics, single crystals have been successfully grown inside templates with ordered porous structures. In these cases, multiple channels are occupied by a single crystal. After careful surveying of these reports, we noticed that these single crystals could be distinguished into two types.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation of networks can help to regulate the properties of monocrystalline coordination polymers. Bare or modified carbon nanotubes could be modified to allow coordination polymers to grow around [ 109 110 ]. This is used to form monocrystalline coordination polymers embedding a fast electron transfer route [ 110 ].…”
Section: Reviewmentioning
confidence: 99%
“…These composites are normally synthesized by mixing a specified amount of CNT with MOF precursors, followed by the in situ growth of MOF crystals. Nice typical images of a ZIF-8/CNT composite are represented in Figure , where a nonionic agent (PVP) was employed to change the crystal size of the MOF component …”
Section: Mof/carbon-based Composite Materialsmentioning
confidence: 99%